2011
DOI: 10.1016/j.bpj.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Three Distinct Modes of Exocytosis Revealed by Amperometry in Neuroendocrine Cells

Abstract: Neurotransmission requires Ca(2+)-dependent release of secretory products through fusion pores that open and reclose (partial membrane distention) or open irreversibly (complete membrane distention). It has been challenging to distinguish between these release modes; however, in the work presented here, we were able to deduce different modes of depolarization-evoked exocytosis in neuroendocrine chromaffin and PC12 cells solely by analyzing amperometric recordings. After we determined the quantal size (Q), even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 35 publications
2
49
1
Order By: Relevance
“…However, the augmentation of the granular content could be a result of compound fusion (i.e., two or more SG that fuse before exocytosis) (50). Previous analysis of amperometric spikes has indicated that different modes of exocytosis could be reflected in several characteristics, such as the spike half-width or spike rise (39,51,52). Moreover, a previous study suggested that amperometric feet correspond to SG with higher content (35), similar to what we observed in our study (Table II).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the augmentation of the granular content could be a result of compound fusion (i.e., two or more SG that fuse before exocytosis) (50). Previous analysis of amperometric spikes has indicated that different modes of exocytosis could be reflected in several characteristics, such as the spike half-width or spike rise (39,51,52). Moreover, a previous study suggested that amperometric feet correspond to SG with higher content (35), similar to what we observed in our study (Table II).…”
Section: Discussionsupporting
confidence: 90%
“…Following cell stimulation, a brief current in the form of spikes can be observed as a consequence of the oxidation of the transmitters released by SG (31,38). This technique allows for the detection of differences in the amount of product secreted per SG and cell (39). Therefore, we studied the effects of CRH and Ag (DNP) on the characteristics of exocytotic events.…”
Section: Crh Induces a High Number Of Fusion Events With A Large Quanmentioning
confidence: 99%
“…The distribution of the exocytotic parameters is asymmetric and strongly deviates from normality, hence, motivating the use of the median in place of the mean. [14],[17],[28],[29] These data reveal that inhibition of dynamin GTPase activity leads to significant decreases in the characteristic peak times, t 1/2 and t fall, in the peak current i p and in the released number of molecules, N . Interestingly, this effect is more important when the concentration of dynasore increases.…”
Section: Resultsmentioning
confidence: 98%
“…Figure 4A reports the scatter plot of Log(Q(fC)) versus Log(I max (pA)) values, where variances are represented by solid curves. Three 2D Gaussian distributions uncovered the existence of different clusters of large, small and SAF events, in analogy with 35 . For all the events we found direct proportionality between Log(Q(fC)) and…”
Section: Detection Of Different Modes Of Exocytosis In Bccsmentioning
confidence: 93%
“…These features make the chip suitable for addressing relevant physiological issues related to the detection of spontaneous and stimulated catecholamine secretion, as well as the discrimination between events associated with complete ("full fusion") and incomplete vesicle fusion ("kiss-and-run" and "kiss-and-stay" exocytosis) 35 . In particular, the relevance of spontaneous and evoked secretion is related to the in vivo supply of catecholamines from the adrenal gland that has to be continuously tuned on the basis of the hormonal need, thus ranging from a basal resting release to a more sustained secretion triggered by continuous cell stimulation mimicking stressful conditions.…”
Section: Introductionmentioning
confidence: 99%